Non-Equilibrium Social Science and Policy Introduction and Essays on New and Changing Paradigms in Socio-Economic Thinking - Johnson, Jeffrey; Nowak, Andrzej; Ormerod, Paul; Rosewell, Bridget; Zhang, Yi-Cheng (Understanding Complex Systems, 2017)
Data-driven Science, Modeling and Theory Building; Methodology of the Social Sciences; Economic Theory/Quantitative Economics/Mathematical Methods; Operation Research/Decision Theory; Complexity